(3cJGH eTcd GdMOjK hHjGfgs - (3CHh HcQeMeO Hf GdMSf Hf ahQc GdCfUGQj GdCUHgGfj, GHf ahQc,J (B406 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd HfYeJg hdG JLQi Ydjg GdCReGf hGdChbGa hdG JdMbI GdfbGFV hGdRjGOGJ s
(3BNQgG (B:s
(3hEf de jcf CQGO Pdc aEfG HjfGg ced HjGf eG CTcd XGgQg ef UMjM GdMOjK s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B489s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs